Exploring the Impact of Liquidity, Profitability, and Triple Bottom Line Disclosure on Company Stock Returns - I Gede Ari Wahyu Anantha; I Ketut Jati (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
Stock returns are a key focus for investors. The significant increase in the number of stock investors in Indonesia since 2020 highlights the need to account for stock price fluctuations to achieve optimal returns. This study aims to examine the effect of liquidity, profitability, and triple bottom line disclosure on stock returns. Using a sample of high-profile companies listed on the Indonesia Stock Exchange between 2020 and 2022, 114 observations were analyzed through multiple linear regression. The findings reveal that profitability positively influences stock returns, while liquidity and triple bottom line disclosure show no significant positive impact.